The Impact of Ownership Structure and Financial Performance on Corporate Social Responsibility (Evidence from Manufacturing Companies Listed in IDX in the period of 2017 – 2022) - Putri Naila Meirizka; Paulus Theodorus Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of ownership structure, namely managerial, institutional, and foreign ownership along with financial performance on firm corporate social responsibility. The research sample comprises of manufacturing companies listed on the Indonesia Stock Exchange in the period the 2017–2022. This study utilized quantitative methods using moderated regression analysis (MRA) with SPSS26. The findings show that managerial ownership has a significant negative effect on CSR. Meanwhile, institutional and foreign ownership has a significant effect on CSR. Moreover, firm financial performance proxied by ROA also positively affect CSR.